Sistema recomendador basado en inteligencia artificial que sugiere rutinas de ejercicios para un envejecimiento activo en adultos pertenecientes a LONGEVITY, mediante una aplicación web móvil - Betancourt Dueñas, Josue David (2023)
The present work plan has been developed for Longevity, an entrepreneurship originating from the city of Ibarra. The aim of this applied research is to create an expert system that recommends exercise routines for individuals in the age range of 50 to 60 years with lumbar problems and obesity. These routines depend on the user's factors and their interest in various exercise categories such as mobility or flexibility, strength, and endurance. To accomplish this, the knowledge base was generated with the assistance of expert trainers dedicated to adult care at Longevity, with the goal of helping individuals lead a healthier lifestyle through physical exercises tailored to the capabilities of different users. Users would have access to this service through the development of a mobile application using Flutter. To carry out the aforementioned tasks, the Scrum agile development methodology was employed as it facilitates realignment of objectives with the system under any circumstances. The development tools used to implement the expert system were Flutter and Supabase, while FETCH technology was chosen to handle user requests. As mentioned earlier, the Flutter SDK was used because it allows for cross-platform development. To manage the exercises and users for this graduation project, a website using Flutter was created, which generates standard code for both mobile and web applications